Audit of Coffee Division Sales Information System at PT. Tunas Immanta Gasindo Cilegon Banten Using Cobit 5 Framework - Restiana, Anti; Auliana, Sigit; Permana, Basuki Rakhim Setya; Aryono, Gagah Dwiki Putra; Mansyuri, Umar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
Information system audit is a testing process to infrastructure technology information for know whether the system is in use and running Can ensure security assets owned.​ Sales information system audits can determine the success of a company. The aim is to find out the audit of the coffee division sales information system at PT. Immanta Buds Gasindo Cilegon-Banten uses the Cobit 5 Framework. Research methods This uses quantitative methods with method combined interviews​ based on COBIT questions, observations done For strengthen results study. This research resulted in the audit process of the coffee division sales information system at PT. Immanta Buds Gasindo Cilegon-Banten already walk well with DSS achieve​ with an average value of 4.05 and a percentage of 81.65%, it can be categorized as Rating L (Large Achieved) where score range >50% to 85 % in part great process has been succeed achieved.